AA amyloidosis treated with tocilizumab: case series and updated literature review. (14th January 2015) - Courties, Alice; Grateau, Gilles; Philippe, Peggy; Flipo, René-Marc; Astudillo, Leonardo; Aubry-Rozier, Bérengère; Fabreguet, Isabelle; Fahd, Wafki; Fain, Olivier; Guggenbuhl, Pascal; Hachulla, Eric; Papo, Thomas; et al.
Abstract: Background : In published case reports, tocilizumab (TCZ) has shown good efficacy for AA amyloidosis in almost all patients. We investigated the efficacy and safety of TCZ in AA amyloidosis in a multicentre study of unselected cases. Methods : We e-mailed rheumatology and internal medicine departments in France, Switzerland and North Africa by using the Club Rhumatismes Inflammation (CRI) network and the French TCZ registry, Registry RoAcTEmra (REGATE), to gather data on consecutive patients with histologically proven AA amyloidosis who had received at least one TCZ infusion. Efficacy was defined as a sustained decrease in proteinuria level and/or stable or improved glomerular filtration rate (GFR) and by TCZ maintenance. Results : We collected 12 cases of AA amyloidosis treated with TCZ as monotherapy (mean age of patients 63 ± 16.2 years, amyloidosis duration 20.6 ± 31.3 months): eight patients had rheumatoid arthritis (RA), six with previous failure of anti-tumor necrosis factor α (anti-TNF-α) therapy. In total, 11 patients had renal involvement, with two already on hemodialysis (not included in the renal efficacy assessment). For the nine other patients, baseline GFR and proteinuria level were 53.6 ± 32.8 mL/min and 5 ± 3.3 g/24 h, respectively. The mean follow-up was 13.1 ± 11 months. TCZ was effective for six of the eight RA patients (87.5%) according to European League Against Rheumatism response criteria (four good and two moderate responders). As expected, C-reactive protein (CRP) level decreased with treatment for 11 patients. Renal amyloidosis ( n  = 9) progressed in three patients and was stabilized in three. Overall, three patients showed improvement, with sustained decrease in proteinuria level (42%, 82% and 96%). Baseline CRP level was higher in subsequent responders to TCZ than other patients ( p  = 0.02). Among the six RA patients with previous anti-TNF-α therapy, amyloidosis was ameliorated in one and stabilized in three. Three serious adverse events occurred (two diverticulitis and one major calciphylaxia due to renal failure). Finally, 7 of 12 (58%) patients continued TCZ. Conclusions : The efficacy of TCZ for AA amyloidosis varies depending on the inflammatory status at treatment onset. Discrepancies between our study of unselected consecutive patients and reported cases may be due to publication bias. These results support further prospective trials of TCZ for AA amyloidosis.